Membangun rasa Nasionalisme dan Cinta Tanah Air melalui Pendidikan Kewarganegaraan di sekolah dasar - Sari, Tri Indah; Sihite, Dorawan Lia; Dharma, Surya; Yunita, Sri; Djufri, Elyas (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to describe how to foster a sense of nationalism and love for the motherland in elementary school children through PKN learning. The research method used in this study uses a qualitative approach with descriptive research based on case studies and literature review which aims to find out how to build a spirit of nationalism and love for the country through civics education learning. This research data was obtained through documentation studies, scientific journals, and scientific articles whose accuracy was ensured. This research analysis technique was carried out by comparing and examining one by one related journals regarding the implementation of the rights and obligations of citizens. This research can be useful for the people of Indonesia, especially in the elementary school environment so that they can foster a sense of nationalism through PKN. Based on the results of the study conducted by the researchers, it was found that the application of PKN subjects had been implemented properly. Elementary school in learning citizenship has a spirit of nationalism and love for the motherland, and citizenship education has a role in increasing the nationalism of elementary school students.